SUSTAINABILITY PERFORMANCE MEASUREMENT OF HASANUDDIN UNIVERSITY THROUGH A GRAPHICAL ASSESSMENT OF SUSTAINABILITY IN UNIVERSITIES (GASU) - Sri Wahyuni; Mohammad Iqbal Bakry; Jurana; Muliati (Assets : Jurnal Ekonomi, Manajemen dan Akuntansi, 2023)
This study aims to analyze the sustainability performance of Hasanuddin University. This study used six assessment dimensions: profile, economic, environmental, social, educational, and interrelated issues and dimensions. For each category, an assessment is given for the university’s factual performance. The method used in this study is descriptive qualitative using GASU (Graphical Assessment of Sustainability in University) tools. The results showed that Hasanuddin University has good sustainability performance in all aspects of sustainability. The highest sustainability value is obtained by the educational aspect (100%) and the social aspect (75%). This aspect brings a high value because Hasanudin University is engaged in developing knowledge and education. The value of sustainability in other aspects, such as profile, economic, and environmental, is still at a good level because the value obtained is not less than 50%. Although Hasanuddin University has a good sustainability performance, there is still a need to improve the aspects of interrelated issues and dimensions (33%) because this aspect has the lowest value.